Stakeholder Perceptions of the Procurement of Goods and Services at the Nusa Tenggara River Region II Office in 2020 - ASBANU, Siki Y. A.; ROZARI, Petrus D E; DJAHA, Ajis Salim Adang (Journal of Governance, Taxation and Auditing, 2023)
This research is a descriptive research with a qualitative approach which was carried out at the Nusa Tenggara River Regional Office II with a total of 25 informants while the types of data in this study were primary data and secondary data which were collected through interview techniques, observation and document tracing. The results of the research based on the grid model from Bryson (2004) found that stakeholder perceptions of the procurement of goods and services at the 2020 Nusa Tenggara River Basin Hall II in terms of; (a) High Interest - Low Power (Subjects) have a bad perception of the procurement of goods and services at the 2020 Nusa Tenggara River Basin Center, while (b) the perception of High Interest - High Power (Players) is that there is a close relationship with project partners that has an impact on the quality and quality of work in the field (c) Low Interest - High Power (Context Setters) have the perception that some PPKs are indicated to be KKN, (d) Low Interest - Low Power (Crowd) have the perception that the project resulting from the procurement of goods and services has quality which is low and (e) Stakeholder perceptions of Aspects that Obstacle the Procurement of Goods and Services at the Nusa Tenggara River Region II Office in 2020 are; (a) the COVID-19 pandemic by making budget adjustments and refocusing, (b) the electronic system still has many weaknesses and (c) bureaucratic governance that needs to be improved.